Infection process in sheath blight of rice caused by Rhizoctonia solani - L. WILLOCQUET; U.S. SINGH, AMITA SINGH, RASHMI ROHILA, S. SAVARY (Indian Phytopathology, 2003)
When Rhizoctonia solani is inoculated on inner surface of rice sheath it first colonized the surface before producing the infection structures like lobate appressoria, bulbous appressoria and infection cushion. The most frequent penetration was by hyphal tips followed by lobate apressoria. Colonization of epidermal and mesophyll cells was both intra- and inter-cellular. Intra-cellular hyphae were thick and deformed. Surface hyphae from primary lesions penetrated the healthy tissue both by hyphal tips as well as branched lobate appressoria. Infection was early (by approx. 12 h) when mycelium instead of sclerotium was used as inoculum. Infection process of leaf lamina and sheath were similar except that infection cushions were observed early (i.e. 24 h after inoculation) and in higher frequency on leaf lamina. On leaf sheath they appeared only after formation of primary lesions.